PENGEMBANGAN NILAI KEBINEKAAN GLOBAL MELALUI PENERAPAN LITERASI BUDAYA DI SMP NEGERI 14 SEMARANG - Hikmah, Iklimatul; Sutono, Agus; Suneki, Sri (FPIPSKR Universitas PGRI Semarang, 2025)
This study was motivated by the finding that some students do not understand the value of global diversity and the suboptimal application of cultural literacy in schools. Thus, it is necessary to develop global diversity values through cultural literacy. The purpose of this study was to determine the development of global diversity values through the application of cultural literacy at SMP Negeri 14 Semarang. This study used a descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study included the curriculum vice principal, PPKn teachers, the P5 facilitator team, and six students. The results of this study indicate that the development of global diversity values is carried out through several strategies, including the integration of diversity values into learning, Pancasila Student Profile (P5) project activities, and habituation programs such as cultural and art literacy. This study concludes that the application of cultural literacy can be a strategic means of fostering global diversity values in schools. This has a positive impact on students' understanding, attitudes, and social skills in appreciating diversity and strengthening national identity.